Some critical aspects of EC development Co-operation - El-Shagi El-Shagi (Intereconomics, 1987)
The range of instruments used by the European Community in its development co-operation with Third World countries is wide and in various respects controversial. The following article illustrates a number of aspects of EC development co-operation that have attracted criticism and makes suggestions for an efficient policy.
Keywords: 330; European Community